John W Kirklin: The Greatest Scientific Cardiac Surgeon of the Century - Md Anisuzzaman, -; Hosain, Nazmul (Cardiovascular Journal, 2021)
John Webster Kirklin was an American cardiothoracic surgeon, prolific author and medical educator who is best remembered for refining John Gibbon’s heart-lung bypass machine via a pump-oxygenator to make feasible under direct vision routine open-heart surgery. His other advances, on which success of heart surgeries depends, including teamwork, developments in establishing the correct diagnosis before surgery and progress in computerized intensive care unit monitoring after open heart surgery. Wayne Miller refers to Dr Kirklin in the 1970s as “arguably the best practicing open heart surgeon anywhere. He was one of cardiac surgery’s most accomplished researchers, a scientist whose mind was sometimes compared, flatteringly, to a computer.” John W Kirklin and Brian G Barratt-Boyes drafted the book ‘Cardiac Surgery’, which is considered as the Bible of the subject. Cardiovasc j 2021; 14(1): 93-96